Modeling of Stick‐Slip Behavior in Sheared Granular Fault Gouge Using the Combined Finite‐Discrete Element Method. Issue 7 (17th July 2018) - Gao, Ke; Euser, Bryan J.; Rougier, Esteban; Guyer, Robert A.; Lei, Zhou; Knight, Earl E.; Carmeliet, Jan; Johnson, Paul A.
Abstract: Sheared granular layers undergoing stick‐slip behavior are broadly employed to study the physics and dynamics of earthquakes. Here a two‐dimensional implementation of the combined finite‐discrete element method (FDEM), which merges the finite element method (FEM) and the discrete element method (DEM), is used to explicitly simulate a sheared granular fault system including both gouge and plate, and to investigate the influence of different normal loads on seismic moment, macroscopic friction coefficient, kinetic energy, gouge layer thickness, and recurrence time between slips. In the FDEM model, the deformation of plates and particles is simulated using the FEM formulation while particle‐particle and particle‐plate interactions are modeled using DEM‐derived techniques. The simulated seismic moment distributions are generally consistent with those obtained from the laboratory experiments. In addition, the simulation results demonstrate that with increasing normal load, (i) the kinetic energy of the granular fault system increases, (ii) the gouge layer thickness shows a decreasing trend, and (iii) the macroscopic friction coefficient does not experience much change. Analyses of the slip events reveal that, as the normal load increases, more slip events with large kinetic energy release and longer recurrence time occur, and the magnitude of gouge layer thickness decrease also tends to be larger; while the macroscopic friction coefficient drop decreases. The simulations not only reveal the influence of normal loads on the dynamics of sheared granular fault gouge but also demonstrate the capabilities of FDEM for studying stick‐slip dynamic behavior of granular fault systems. Key Points: The combined finite‐discrete element method provides a powerful approach to modeling stick‐slip behavior in granular fault gouge The number of slip events with large kinetic energy release and gouge layer thickness drop increases with increasing normal load As normal load increases, the earthquake reoccurrence (interevent) time tends to be longer